ANALYSIS OF TRANSLATION SHIFT IN BILINGUAL CHILDREN'S STORYBOOKS - Tri Widarwati, Nunun; Purnomo, Budi; Indri Astuti, Purwani; Wijayava, Ratih (University of Kuningan, 2024)
lingual illustrated children's stories are excellent tools for teaching English to beginners, particularly children. Translating such stories requires the use of simple and easily understandable language to aid children's growth and development. Thus, it is crucial that translation shifts in children's stories effectively convey meaning and are suitable for young learners. This study focuses on the translation shifts in the illustrated bilingual children's story